Globoid cell leukodystrophy in two dachshund siblings. Issue 2 (21st January 2022) - Kosinova Pausova, Tereza; Rosati, Marco; Tomek, Aleš
Abstract: An 11‐week‐old male dachshund and its 13‐week‐old female sibling presented with slowly progressive gait abnormalities, cerebellar ataxia and intention head tremor. In the pedigree of their parents, there were no signs of these neurological abnormalities. The magnetic resonance imaging scan results, cerebrospinal fluid and complete blood analysis obtained in the male dog were not consistent with metabolic, infectious or anomalous conditions, leaving a degenerative disorder as the most likely differential diagnosis. Both puppies were euthanased (male after 3 weeks and female after 6 weeks) due to diffuse central nervous system abnormalities. Histopathology findings were consistent with globoid cell leukodystrophy. To the authors' knowledge, this is the first confirmed case of this lysosomal storage disease in a dachshund.